2016
DOI: 10.1165/rcmb.2015-0243oc
|View full text |Cite
|
Sign up to set email alerts
|

Rhinovirus Delays Cell Repolarization in a Model of Injured/Regenerating Human Airway Epithelium

Abstract: Rhinovirus (RV), which causes exacerbation in patients with chronic airway diseases, readily infects injured airway epithelium and has been reported to delay wound closure. In this study, we examined the effects of RV on cell repolarization and differentiation in a model of injured/regenerating airway epithelium (polarized, undifferentiated cells). RV causes only a transient barrier disruption in a model of normal (mucociliary-differentiated) airway epithelium. However, in the injury/regeneration model, RV pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 50 publications
2
35
1
Order By: Relevance
“…Since RV activates EGFR and induces acute expression of MUC5AC in normal epithelial cells,34 35 and GCH in repairing airway epithelial cell cultures,15 we reasoned that RV-induced EGFR may contribute to the observed GCH in COPD. To our surprise, RV did not increase EGFR phosphorylation in COPD cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Since RV activates EGFR and induces acute expression of MUC5AC in normal epithelial cells,34 35 and GCH in repairing airway epithelial cell cultures,15 we reasoned that RV-induced EGFR may contribute to the observed GCH in COPD. To our surprise, RV did not increase EGFR phosphorylation in COPD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mucociliary-differentiated cell cultures were infected apically with 10 µL of phosphate buffered saline (PBS) containing RV16 at 1 multiplicity of infection (MOI) or equivalent volume of sham and incubated for 15 days as described previously 15. Medium in the basolateral chamber was changed every other day.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sajjan et al (2008) showed that infection of polarized airway epithelial cells with HRV can lead to redistribution of the tight junction protein zona occludens 1 (ZO-1) from the membrane to the cytoplasm. Furthermore, HRV was shown to impair the repolarization of airway epithelium regenerating after injury (Faris et al, 2016). Integrity of the epithelial barrier likewise is reduced after RSV infection (Kilani et al, 2004).…”
Section: Compromising the Epithelial Barrier Functionmentioning
confidence: 99%